Antinociceptive efficacy of levetiracetam in a mice model for painful diabetic neuropathy - Ozcan, M.; Ayar, A.; Canpolat, S.; Kutlu, S. (Wiley, 2008)
Background and Objective: Despite important advances in available knowledge, management of neuropathic pain remains incomplete, and results from experimental and clinical studies indicate that some anticonvulsants show promise for treating neuropathic pain. The aim of this study was to assess the antinociceptive efficacy of levetiracetam (LEV, ucb L059) in a mice model for painful diabetic neuropathy using the in vivo nociceptive behavioral 'hot-plate test.' Methods: The hot-plate test consisted of placing individual mice (adult male Balb/C) on the hot plate at 50 +/- 0.1 degrees C and timing the delay for the first hind paw lift (nociceptive threshold). After obtaining control values, diabetes was induced by injection of streptozotocin [200 mg/kg intraperitoneally (i.p.)] and 2 weeks after induction of diabetes (serum glucose >= 400 mg/dL) LEV was administered i.p. and hot-plate tests were repeated. Pain threshold values were determined and analyzed by Kruskal-Wallis one-way analysis of variance (ANOVA) followed by a pairwise comparison using a Dunnett's t-test on the ranked data. Results: LEV (60, 300 and 900 mg/kg) had no significant effect on the nociceptive threshold in normal mice (n=8 for each dose, P > 0.05). There were significant decreases in pain threshold latency in diabetic mice compared with the normal healthy group and these were significantly and dose-dependently restored by much lower doses of LEV (20, 100 and 200 mg/kg) in a reversible manner. Conclusion: Results obtained from the in vivo behavioral test lend support to the validation of the promising therapeutic potential of the novel antiepileptic agent LEV in the treatment of neuropathic pain.
Joint Meeting of the Biochemical-Society/British-Pharmacological-Society/Physiological-Society -- JUL 08-12, 2007 -- Glasgow, SCOTLAND
Keywords: levetiracetam; painful diabetic neuropathy; mice